Favourable outcome of combined medical surgical treatment of cerebral aspergillosis of pulmonary origin. Issue 6 (18th December 2015) - Ruiz-Santana, Sergio; Cabrera-Arrocha, Jesús; Hernández-Socorro, Carmen-Rosa; Paz-Cruz, Inmaculada; Campos-Herrero, María-Isolina; León-Gil, Cristóbal
Abstract : Introduction: Cerebral aspergillosis is a highly fatal infection. Its origin is most likely blood-borne from the lungs and most patients are immunosuppressed. Mortality is over 90 % and the treatment chosen is key for survival. Case presentation: We report a 32-year-old female with a history of acute myeloid leukaemia (M3) who was admitted to the hospital due to a nodular infiltrate in the right superior lobe. A lung computed tomography (CT) scan displayed a right upper lobe cavitated nodule. A brain CT scan showed a right hemisphere deep abscess. Pulmonary aspergillosis was diagnosed after bronchoalveolar lavage. Three weeks later, while on antifungal treatment with voriconazole and liposomal amphotericin B, she suffered left motor focal deficits, and brain abscess puncture and aspiration by neuronavigation were performed for diagnosis and decompression. A PCR assay was positive for Aspergillus fumigatus . One week later, she developed an intraventricular brain haemorrhage requiring external ventricular drainage and intrathecal fibrinolysis with recombinant tissue plasminogen activator. She eventually achieved a good neurological outcome. A control brain CT showed an important reduction in mass size. Conclusion: Antifungal treatment is the mainstay for brain abscess treatment, and its combination with stereotactic needle aspiration is a better option compared with open surgery, particularly in abscesses located in deep motor areas.